(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: The purpose of this study was to determine the effect on the performance of the ethics office at the State Secretariat of Civil Administrative Region city of Manado. The method used is the method of quantitative research korelasional.Responden are 36 people ASN / PNS taken by random sampling technique of structural official and executive employees / staff at the Regional Secretariat Manado.Data used is primary data collected using questionnaires and assisted with interview techniques. The analysis technique used is a simple linear regression analysis and simple correlation / product moment. The result showed: (1) variable regression coefficient ethics office to the level of performance of the apparatus is very significant posifive and (2) the correlation coefficient and the coefficient of determination variables ethics office to the performance of the apparatus is high / strong and highly significant. Based on the results of these studies conclude is ethics office have functional relations / positive and significant impact on the performance of the State Civil Apparatus (PNS) in the Regional Secretariat of Manado. According to the conclusion that the ethics office let be used as a tool or a means to improve the performance of the State Civil Apparatus. Keywords: ethics office, the performance of the apparatus.